Impedance, circuit simulation, transport properties and energy storage behavior of plasticized lithium ion conducting chitosan based polymer electrolytes - Shujahadeen B. Aziz; Ahmad S.F.M. Asnawi; Pshko A. Mohammed; Rebar T. Abdulwahid; Yuhanees M. Yusof; Ranjdar M. Abdullah; M.F.Z. Kadir (Polymer Testing, 2021)
In this work, energy storage devices based on plasticized chitosan biopolymer electrolytes were studied. The polymer electrolyte system of CS-LiClO4 with three different glycerol concentrations has been well prepared. The FTIR analysis revealed that the glycerol has interacted with the CS-LiClO4complex, which is confirmed bythe existence of several functional groups. The results of impedance spectroscopy were fitted with electrical equivalent circuits. The ion transport parameters were analyzed from the deconvoluted FTIR spectra. The highest ionic conductivity is obtained at 1.20 × 10−3 S cm−1 for CS-LiClO4 doped with 30 wt% glycerol (C3) with the breakdown voltage of 2.13 V. The transport parameters are observed to be influenced by the ionic conductivity, which verified from the deconvolution of v(ClO4−) band. The dielectric and electric modulus studies revealed the non-Debye behavior of the electrolytes.The tionvalue for C3 was 0.955 while telec was 0.045, and these values were used to further evaluate the contribution of ionsin ionic mobility and diffusion coefficient. At the scanned rate of 10 mV s−1, the maximum Cs value was obtained to be 98.99 F/g by the EDLC, very similar to the Cs (97.98 F/g) extracted from the 1st cycle GCD curve. Other parameters such as energy density and power density are specified for the fabricated EDLC device.